2022
DOI: 10.20882/adicciones.1778
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia de un programa de tratamiento en el consumo de drogas en menores infractores desde la psicología positiva

Abstract: Eficacia de un programa de tratamiento en el consumo de drogas en menores infractores desde la psicología positiva

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…However, our study with young offenders found that the contingency management program positively contributed to a reduction in relapses into cannabis use during juvenile detention; that is, relapses were less frequent among participants with whom the contingency management program was applied. These results are in line with those of Fernández-Moreno et al (2022), who found evidence of the effectiveness of interventions based on cognitivebehavioural models applied using a paradigm of positive psychology to reduce the problems associated with alcohol and drug consumption among juvenile offenders. These results are particularly noteworthy given the limited effectiveness of intervention programs aiming to address substance abuse, including cannabis (Tanner-Smith et al, 2016).…”
Section: Type Of Drugsupporting
confidence: 91%
See 4 more Smart Citations
“…However, our study with young offenders found that the contingency management program positively contributed to a reduction in relapses into cannabis use during juvenile detention; that is, relapses were less frequent among participants with whom the contingency management program was applied. These results are in line with those of Fernández-Moreno et al (2022), who found evidence of the effectiveness of interventions based on cognitivebehavioural models applied using a paradigm of positive psychology to reduce the problems associated with alcohol and drug consumption among juvenile offenders. These results are particularly noteworthy given the limited effectiveness of intervention programs aiming to address substance abuse, including cannabis (Tanner-Smith et al, 2016).…”
Section: Type Of Drugsupporting
confidence: 91%
“…For this group, in addition to the therapy provided at the CEMJTC (Fernández-Moreno et al, 2022), random drug testing protocol was conducted after their return to the Centre after leave permits for education, employment or recreation. No actions were taken in the event of negative results (no consumption); in the case of a positive result (repeat of drug consumption) a disciplinary report was created, part of the general action protocol for the Centre.…”
Section: Active Quasi-control Groupmentioning
confidence: 99%
See 3 more Smart Citations